Activation of the ileal neuroendocrine tumor cell line P-STS by acetylcholine is amplified by histamine: role of H3R and H4R - Beatrix Pfanzagl (Nature Portfolio, 2017)
Abstract Neuroendocrine tumors may present with pseudoallergic reactions like diarrhea and idiopathic anaphylaxis. Here we present the P-STS human ileal neuroendocrine cell line as a model cell line for these tumors. Neuroendocrine markers and changes in cytoplasmic calcium concentration ([Ca2+]i) in response to several possible activators of 5-hydroxytryptamine (﻿5-HT) release were analyzed. P-STS cells still expressed chromogranin A and synaptophysin after 2 years of culture. Tryptophan hydroxylase 1 mRNA and a low amount of 5-HT were also detected. Acetylcholine (ACh) caused a rise in [Ca2+]i. Somatostatin inhibited, whereas histamine (HA) but not the HA receptor ligand betahistine enhanced activation by ACh. The [Ca2+]i response to ACh/HA was inhibited by the HA receptor H3 (H3R) agonist methimepip and by the antidepressant imipramine. Further [Ca2+]i response studies indicated the presence of H4Rs and of a functional calcium sensing receptor. High or low affinity IgE receptor protein or mRNA were not detected. Taken together, neuroendocrine markers and response to intestinal neurotransmitters approve the P-STS cell line as a valuable model for enterochromaffin cells. Enhancement of their ACh-induced pro-secretory response by HA, with a role for H3R and H4R, suggests an amplifying role of neuroendocrine cells in allergen-induced diarrhea or anaphylaxis.